2016
DOI: 10.1016/j.jbiomech.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a new uniform thorax density representative of the living population from 3D external body shape modeling

Abstract: Body segment parameters (BSP) for each body׳s segment are needed for biomechanical analysis. To provide population-specific BSP, precise estimation of body׳s segments volume and density are needed. Widely used uniform densities, provided by cadavers׳ studies, did not consider the air present in the lungs when determining the thorax density. The purpose of this study was to propose a new uniform thorax density representative of the living population from 3D external body shape modeling. Bi-planar X-ray radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…1), and patients who did not respect this position were excluded. This significantly limits the uncertainty of the gravity line position, as was confirmed by validation studies on healthy subjects and scoliotic patients, which reported an uncertainty of the GL position lower than 9 mm [10,14].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…1), and patients who did not respect this position were excluded. This significantly limits the uncertainty of the gravity line position, as was confirmed by validation studies on healthy subjects and scoliotic patients, which reported an uncertainty of the GL position lower than 9 mm [10,14].…”
Section: Discussionmentioning
confidence: 78%
“…For each vertebra, the body segment above it (ie, the sum of the slices above it) was characterized by calculating its volume. Using the estimation of the density values proposed by Dempster [13] and by Amabile for the torso [14], its mass and center of mass (COM segment ) were also computed. The subject's arms were included in the model, although their position was not personalized, and their weight was shared by the T2 and T3 vertebrae.…”
Section: Barycentremetrymentioning
confidence: 99%
“…The lung volume and capacity were higher in male mongoose than in female was parallel to the morphometric measurements of the lungs, which had greater values in the former compared to the latter (Guyton, 1986). Amabile et al (2016) assessed the 3D reconstruction model of the human thorax and found the thorax and lung volumes to be greater in males than in females. However, there was no significant difference observed in human fetal lung volumes due to genders (Szpinda et al, 2015).…”
Section: Resultsmentioning
confidence: 78%
“…Pelvic tilt (PT): angle between the line connecting the center of the femoral heads and the middle of the sacral plate and the vertical. Sacral slope (SS): angle between the sacral plate line and the horizontal [11,13]; c OD-HA, adapted from Amabile et al [20]: angle between the line joining the most superior point of dentiform apophyse of C2 (OD) and the middle of acetabulum centers (HA) with the vertical, which is an invariant parameter in the young and in the elderly general populations [20,22]. In a balanced posture, the head is over the pelvis and the OD-HA is close to zero; d Sagittal vertical axis: SVA, adapted from Diebo et al [32]: posteroanterior distance between the C7 plumb line and the posterosuperior point of the sacral plate.…”
Section: Ethicsmentioning
confidence: 99%
“…In the general population, it is now accepted that a misalignment could induce an imbalanced or noneconomical posture, causing an increase in the loads on the spinal structures. Subsequently, it can cause a overuse of trunk muscles to compensate the imbalance [5][6][7][8][9][10][11]. Thus, changes in the spinal posture can lead to pain due to premature lesions of structures and muscular efforts.…”
Section: Introductionmentioning
confidence: 99%